1995
DOI: 10.1097/00004714-199510000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Free Radical Scavenging Enzyme Activity and Related Trace Metals in Clozapine-Induced Agranulocytosis

Abstract: We hypothesized that patients who had experienced clozapine-induced agranulocytosis would have abnormalities in their free radical scavenging enzyme activity (FRESA) and levels of related trace metals. We therefore measured FRESA profiles and related trace metals in four groups: post-clozapine agranulocytosis (POST CLOZ AGRAN) (N = 9); clozapine no agranulocytosis (CLOZ NO AGRAN) (N = 12); West Coast controls (WC CONTROLS) (N = 14); and Long Island Jewish Medical Center controls (LIJ CONTROLS) (N = 12). Glutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 23 publications
0
7
1
Order By: Relevance
“…Unfortunately it also has severe side‐effects, notably agranulocytosis, myocarditis and cardiomyopathy, which can cause death and sometimes sudden death in otherwise stable patients [6, 7]. In a small study of clozapine‐treated patients, the group that developed agranulocytosis and the group that did not had lower plasma selenium concentrations than normal controls [8]; however, the authors did not measure red‐cell selenium concentrations, and no comparisons were made with schizophrenic patients not treated with clozapine or with other psychiatric patients.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately it also has severe side‐effects, notably agranulocytosis, myocarditis and cardiomyopathy, which can cause death and sometimes sudden death in otherwise stable patients [6, 7]. In a small study of clozapine‐treated patients, the group that developed agranulocytosis and the group that did not had lower plasma selenium concentrations than normal controls [8]; however, the authors did not measure red‐cell selenium concentrations, and no comparisons were made with schizophrenic patients not treated with clozapine or with other psychiatric patients.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] Both extracellular and intracellular defenses protect the host from free radical-mediated injury. [18][19][20][21][22][23] Preexisting genetically determined variations in baseline free radical scavenging enzyme activities or trace element concentrations could play an important role in explaining these clinically observable differences. [18][19][20][21][22][23] Preexisting genetically determined variations in baseline free radical scavenging enzyme activities or trace element concentrations could play an important role in explaining these clinically observable differences.…”
mentioning
confidence: 99%
“…Extracellar defenses include a variety of proteins (eg, albumin, transferrin, and ceruloplasmin).14,15 Five intracellular free radical scavenging enzymes provide the major antioxidant defense: glutathione peroxidase, glutathione reductase, glutathione-Stransferase, catalase, and superoxide dismutase.l6 The trace elements selenium (Se), copper (Cu), and zinc (Zn) are essential for the proper functioning of these enzymes Clinically, some of these free radical-mediated illnesses demonstrate differences in their prevalence and outcome based on age, sex, ethnicity, and race. [18][19][20][21][22][23] Preexisting genetically determined variations in baseline free radical scavenging enzyme activities or trace element concentrations could play an important role in explaining these clinically observable differences. Erythrocyte glutathione peroxidase and superoxide dismutase are the most important enzymes involved in the pathophysiology of free radical-mediated neurologic diseases .…”
mentioning
confidence: 99%
“…Further, sodium valproate has been shown to decrease the synthesis of glutathione peroxidase, thus inhibiting the production of the antioxidant glutathione (Pippenger et al 1992). The rapid reduction of nitrenium ions may be limited by valproates inhibition of glutathione production, which may contribute to or trigger the generation of excess free ions, leading to neutropenia (Linday et al 1995). This suggests that the combined effect on cell activation by clozapine and sodium valproate, combined with reduced glutathione production induced by valproate, may lead to increased reactive metabolites, leading to neutrophil toxicity and apoptosis.…”
Section: Putative Mechanism Of Clozapine and Valproate Associated Neumentioning
confidence: 99%
“…Another potential mechanism for the increased risk for neutropenia relates to shared actions on cytokines. Both clozapine (Sperner-Unterweger et al 1993) and sodium valproate (Linday et al 1995) have been shown to inhibit the production of granulocyte-macrophage colony stimulating factor (GM-CSF) in vitro, thus reducing granulopoiesis and thus limiting the compensatory mechanisms against the increased rate of neutrophil destruction.…”
Section: Putative Mechanism Of Clozapine and Valproate Associated Neumentioning
confidence: 99%